(untitled) (Revista de Ciências Agroveterinárias, 2006)
Brazil has one of most diversified flora of the world, having the possibility of a rich set of medicinal plants. The local people who have diary experience with these vegetal resources have been fundamental importance to their management and conservation. The Ethnobotany, with its theoretical and methodological set can help to concretize the dialogue between scientific knowledge and knowledge and experiences of human communities of most diverse regions. The different approach strategies of conservation, aiming to conciliate the use with the conservation of natural, social and cultural resources by instruments that are available by Ethnobotany is the main focus of this article.